EDUCATIONAL QUALITY IS AN IMPORTANT FACTOR IN FURTHER IMPROVING THE DEVELOPMENT OF NEW UZBEKISTAN - Tolipova Zebuniso Ulugbek qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes the higher education system of the Republic of Uzbekistan. The reforms implemented in the field of development were discussed.